Risk Factors of Breast Cancer in Women at Dr. Moewardi Hospital, Surakarta, Central Java - Yana Listyawardhani; Ambar Mudigdo; Rita Benya Adriani (Journal of Epidemiology and Public Health, 2018)
Background: Breast cancer is a leading type of cancer affecting women around the world. Its incidence is increasing in developed and developing countries. Breast cancer is the leading cause of death among women in Indonesia with 19,731 cases of death in 2014. In addition to mortality, breast cancer causes psychosocial effect in the affected and the family. This study aimed to determine the risk factors of breast cancer in women at Dr. Moewardi Hospital, Surakarta, Central Java.Subjects and Method: This was an analytical observational study with case control design. The study was conducted at Dr. Moewardi Hospital, Surakarta, from October to December, 2017. A total sample of 200 study subjects consisting of 100 women with breast cancer and 100 women without breast cancer were selected for this study by fixed disease sampling. The dependent variable was breast cancer. The independent variables were age at menarche, age at first pregnancy, parity, duration of breastfeeding, use of fertility hormone, duration of hormonal contraceptive use, and age at menopause. The data was collected  by questionnaire and analyzed by multiple logistic regression.Results: The risk of breast cancer increased with earlier age at menarche <12 years old (OR= 2.71; 95% CI= 1.06 to 6.96; p= 0.037), delayed age at first pregnancy ≥30 years old (OR=3.01; 95% CI= 1.16 to 7.78; p= 0.023), delayed age at menopause ≥55 years old (OR=1.07; 95% CI=0.82 to 6.30; p= 0.001), longer hormonal contraceptive use ≥10 years (OR=3.25; 95% CI= 1.20 to 9.63 p= 0.003).Conclusion: The risk of breast cancer increases with earlier age at menarche, delayed age at first pregnancy, delayed age at menopause, longer hormonal contraceptive use.Keyword: Breast Cancer, Risk FactorCorrespondence: Yana Listyawardhani. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email:yanalistya@gmail.comJournal of Epidemiology and Public Health (2018), 3(2): 118-127https://doi.org/10.26911/jepublichealth.2018.03.02.02